Auditory brain stem response screening for hearing loss in high risk neonates - (:unkn) unknown (Elsevier Ireland Ltd, 2000)
Hearing screening of neonates is the key to preventing the most severe consequences of congenital hearing loss. In this paper, the auditory brain stem responses (ABR) of neonates at high risk for hearing impairment at Marmara University Hospital Neonatal Intensive Care Unit are reported. One hundred fifty-four high-risk neonates underwent screening by ABR carried out according to the US Joint Committee on Hearing 1994 Position Statement. One hundred and fourteen of them passed the first ABR test while 40 patients failed. The number of patients with sensorineural and conductive hearing deficit was 5 and 35, respectively. Fifteen of the infants who failed had bilateral hearing loss. During follow-up, 6 of these 40 infants (15%) failed subsequent tests. Two of these babies had bilateral involvement, and the rest had unilateral involvement. The infant with bilateral sensorineural hearing loss had a cochlear implantation. Seventeen of the 40 infants passed the second ABR (42%). Three patients did not survive and 11 (27%) werelost from the follow-up. Three patients who failed the first ABR were scheduled to have the second ABR soon afterwards. It is concluded that early diagnosis of hearing loss in high risk neonates is important for the implementation of hearing aids early in infancy so as to prevent acoustic deprivation.
Keywords: Auditory brain stem response; Hearing loss; Newborn